Identification and Characterization of TspA, a Major CD4(+) T-Cell- and B-Cell-Stimulating Neisseria-Specific Antigen - Kizil, Goksel (American Society for Microbiology, 1999)
In search for novel T-cell immunogens involved in protection against invasive meningococcal disease, we screened fractionated proteins of Neisseria meningitidis (strain SD, B:15:P1.16) by using peripheral blood mononuclear cells (PBMCs) and specific T-cell lines obtained from normal individuals and patients convalescing from N. meningitidis infection. Proteins of iron-depleted meningococci produced higher PBMC proliferation indices than proteins of iron-replete organisms, indicating that iron-regulated proteins are T-cell immunogens. Insoluble proteins of the iron-depleted cells, which produced better T-cell stimulation than soluble ones, were fractionated by using sodium dodecyl sulfate-polyacrylamide gels and recovered as five fractions (F1 to F5) corresponding to decreasing molecular weight ranges. The proteins were purified (by elution and precipitation) or electroblotted onto nitrocellulose membranes (dissolved and precipitated) before use in further T-cell proliferation assays. One of the fractions (F1), containing high-molecular-mass proteins (>130 kDa), consistently showed the strongest T-cell proliferation responses in all of the T-cell lines examined. F1 proteins were subdivided into four smaller fractions (F1A to F1D) which were reexamined in T-cell proliferation assays, and F1C induced the strongest responses in patients’ T-cell lines. Rabbit polyclonal antibodies to F1C components were used to screen a genomic expression library of N. meningitidis. Two major clones (C1 and C24) of recombinant meningococcal DNA were identified and fully sequenced. Sequence analysis showed that C24 (1,874 bp) consisted of a single open reading frame (ORF), which was included in clone C1 (2,778 bp). The strong CD4(+) T-cell-stimulating effect of the polypeptide product of this ORF (named TspA) was confirmed, using a patient T-cell line. Immunogenicity for B cells was confirmed by showing that convalescent patients’ serum antibodies recognized TspA on Western blots. Additional genetic sequence downstream of C24 was obtained from the meningococcal genomic sequence database (Sanger Centre), enabling the whole gene of 2,761 bp to be reconstructed. The DNA and deduced amino acid sequence data for tspA failed to show significant homology to any known gene, except for a corresponding (uncharacterized) gene in Neisseria gonorrhoeae genome sequences, suggesting that tspA is unique to the genus Neisseria. The DNA and deduced amino acid sequence of the second ORF of clone C1 showed significant homology to gloA, encoding glyoxalase I enzyme, of Salmonella typhimurium and Escherichia coli. Thus, we have identified a novel neisserial protein (TspA) which proved to be a strong CD4(+) T-cell- and B-cell-stimulating immunogen with potential as a possible vaccine candidate.